2018
DOI: 10.1186/s12884-018-2115-4
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal outcomes of singleton pregnancies conceived via assisted reproductive technology complicated by gestational diabetes mellitus: a prospective cohort study

Abstract: BackgroundGrowing evidence indicates that the risk of obstetric and perinatal outcomes is higher in women with assisted reproductive technology (ART). However, there is little known about pregnancy related complications and co-morbidity in gestational diabetes mellitus (GDM) following singleton pregnancies achieved by ART in comparison with spontaneous conception (SC).MethodsTwo hundred sixty singleton pregnant women conceived by ART and 314 pregnant women conceived by spontaneous conception (SC) were particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 43 publications
(43 reference statements)
5
20
0
Order By: Relevance
“…[61,62]. However, in most cases involving humans, no immediate abortion has been observed, and most women give birth successfully after IVF-ET, which supports the hypothesis that interference by IVF-ET can trigger a placental compensatory mechanism [63,64].…”
Section: Discussionmentioning
confidence: 76%
“…[61,62]. However, in most cases involving humans, no immediate abortion has been observed, and most women give birth successfully after IVF-ET, which supports the hypothesis that interference by IVF-ET can trigger a placental compensatory mechanism [63,64].…”
Section: Discussionmentioning
confidence: 76%
“…There have been many debates on the efficacy and safety of using ART regarding its increasing trend of use across most countries [77,78]. It has been shown that ART is responsible for a high number of adverse pregnancyrelated complications and obstetric outcomes such as polyhydramnios, low and very low infant birth weight, pregnancy-induced hypertension, pre-eclampsia, perinatal mortality, preterm and very preterm birth, placenta [79][80][81][82][83]. As mentioned, using ART was associated with GDM, which is diabetes diagnosed during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The fallopian tube is the most common site of ectopic implantation [8] , and about 1.5-2.1% of patients with ectopic pregnancy have undergone IVF [7] . Our findings showed that the percentage of women with a history of ectopic pregnancy was higher in the ET group (15.3%) than in the NC group (2.7%), which may be associated with previous ectopic pregnancy, history of infertility, history of surgery or the use of intrauterine contraceptive device [9] .…”
Section: Discussionmentioning
confidence: 54%